Spindle cell carcinoma of the larynx: a rare entity - Ramakrishnan, Rajika; Natarajan, Kiran; Kamath, Sreenivas; ., Susruthan; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Squamous cell carcinoma (SCC) is the commonest malignancy encountered in the larynx in the Indian population. Spindle cell carcinoma is an extremely rare malignant tumor and is a variant of SCC with a mesenchymal like malignant cell component. This is a case report of a 58 years old patient who presented with hoarseness of voice of 7 months duration. He was diagnosed to have a right vocal cord polypoidal growth with mobile vocal cords. He underwent direct laryngoscopy and biopsy of the lesion which was reported as spindle cell neoplasm/inflammatory myofibroblastic tumor (IMT). Immunohistochemistry (IHC) was carried out and confirmed the diagnosis of inflammatory myofibroblastic tumor. He was doing well and the follow up videolaryngoscopic examinations and PET CT were normal. At subsequent follow-up 19 months later, he was found to have a recurrent right vocal cord lesion. Direct laryngoscopy and biopsy was repeated along with laserization of the right vocal cord. Histopathology was reported as spindle cell malignant neoplasm. Immunohistochemistry was reported as spindle cell carcinoma. He was then sent for radiation therapy. The patient responded well to radiation and is tumor free at last follow-up. He has been advised regular follow-ups. Spindle cell carcinoma is an extremely rare laryngeal malignancy. It typically originates in the glottis. The treatment for spindle cell carcinoma includes surgery, radiation or a combination of these modalities. Its prognosis is worse than squamous cell carcinoma and patients require close follow-ups.